Quality Characteristics of Palm Olein in Frying Systems - Asap, Telingai (1985)
The changes in quality characteristics of refined bleached and deodorised palmole in (RBD olein)during heating and heating with intermittent frying for 5hr/day for 8 consecutive days in 4 different systems were studied.The systems studied included (1)static heating of RED olein without antioxidant,(2)heating with intermittent frying using RBD olein without antioxidant,(3)heating with intermit tent frying using RBD olein to which 200 ppm of tertiary butylhydroquinone had been added prior to frying on the first day and (4) heating with intermittent frying using RBD olein which had tertiary butylhydroquinone topped up to a level of 200 ppm at the start of each day.The evaluation of oil quality included assessment of colour, iodine value, fatty acid composition, C18:2 remaining (%), polar components , dielectric constant, acid value, smoke point, polymers'content and uv absorbance at 232nm and 268 nm. The results showed that oil deterioration increases with increase sin heating and frying time.The useful frying life of RBD olein under these conditions is about 4 days when 27.0% polar components is taken as the accepted limit for frying oil. The addition of tertiary butylhydroquinone has some protective effect on the oil. This is most evident in system 4. The only observed undesirable effect of tertiary butylhydroquinone is that it caused darkening of the oil.